2017
DOI: 10.12659/ajcr.899687
|View full text |Cite
|
Sign up to set email alerts
|

Late-Onset Cerebral Toxoplasmosis After Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Patient: Male, 44Final Diagnosis: Cerebral toxoplasmosis after HSCTSymptoms: Hemiparesis • muscle weaknessMedication: —Clinical Procedure: —Specialty: HematologyObjective:Unusual clinical courseBackground:Toxoplasmosis is an uncommon but potentially fatal complication following allogeneic hematopoietic stem cell transplantation (HCT). Post-transplant toxoplasmosis is often a reactivation of prior infection and typically occurs within the first 6 months of transplant. Herein, we report that cerebral toxoplasmos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
0
10
0
2
Order By: Relevance
“…Similarly, Etewa et al, [49] in their histopathological study of brain sections of spiramycin treated mice, reported the presence of few numbers of Toxoplasma cysts encircled by mild inflammatory cellular reaction. These findings were explained by Khalaf et al, [50] , who attributed these changes to immunosuppression that flares up cerebral toxoplasmosis. In our study, the recorded reaction may be due to the infection itself or the response to the tested SCs.…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, Etewa et al, [49] in their histopathological study of brain sections of spiramycin treated mice, reported the presence of few numbers of Toxoplasma cysts encircled by mild inflammatory cellular reaction. These findings were explained by Khalaf et al, [50] , who attributed these changes to immunosuppression that flares up cerebral toxoplasmosis. In our study, the recorded reaction may be due to the infection itself or the response to the tested SCs.…”
Section: Discussionmentioning
confidence: 89%
“…PCR techniques have been developed for noninvasive diagnosis, and can also be used for the diagnosis of cerebral toxoplasmosis, which contribute to rapid diagnosis and monitoring of treatment efficacy. However, to avoid false negative results of PCR, some authors still emphasize the role of serology in the diagnostics of toxoplasmosis, as well as a combination of serology and PCR techniques . Hu et al .…”
Section: Discussionmentioning
confidence: 99%
“…The risk of reactivation correlates with the degree of immunosuppression and is associated with low CD4 þ lymphocyte counts [23,24]. Toxoplasmosis usually develops within the first 6 months after allogeneic HCT, with a peak incidence in the second and third months [5,25]. However, late cases of toxoplasmosis beyond the first 6 months may occur in the context of chronic graft-versus-host disease and its treatment [26,27].…”
Section: Epidemiology and Acquisition Of The Organismmentioning
confidence: 99%